Drivers of Mobility of Chinese and Indian Students - Choudaha, Rahul (International Higher Education, 2011)
India and China are becoming increasingly influential, not only in the global economy but also in the supply of globally mobile students. Regarding Chinese and Indian students, on the supply side, two key drivers are increasing prosperity, which enables the ability to afford foreign education, and rapid expansion of the system of higher education at the expense of quality. On the demand side, two key drivers are universities' aggressive approach to recruiting students to compensate for budget cuts and access to a wider range of recruitment channels and service providers.